Advances in Ion Conducting Membranes and Binders for High Temperature Polymer Electrolyte Membrane Fuel Cells. (2nd October 2022) - Jung, Jiyoon; Ku, Jinsuk; Park, Young Sang; Ahn, Cheol-Hee; Lee, Jung-Hyun; Hwang, Seung Sang; Lee, Albert S.
Abstract: This review article provides an overview of the latest developments in polymer electrolytes, the ion conducting membrane and ionomeric binder, specially tailored for high temperature polymer electrolyte membrane fuel cells that operate at temperatures exceeding 100 °C without the assistance of humidification. This particular type of fuel cell have the added advantages of high CO tolerance, enhanced catalytic activity, and system simplification. While high temperature polymer electrolyte membrane fuel cells utilizing phosphoric acid-doped polybenzimidazole membranes have been extensively investigated and commercialized over the past half century, recent developments in alternative polymeric materials and their synergistic integration with newly applied ionomeric materials have been introduced, warranting a closer look at the chemistry and properties of such materials in conjunction with those developed previously. General background in high temperature polymer electrolyte membrane fuel cells, and as well as developments in various classification of membranes, ionomers, concluding with future challenges and outlook on high temperature polymer electrolyte membrane and ionomer technology is addressed from the vantage point of the membrane electrode assembly.